Kurikulum Integratif Dan Ppengaruhnya Terhadap Kompetensi Lulusan : Studi Pada Fakultas Ekonomi International Islamic University Malaysia - Nurhidayat Nurhidayat; Sadari Sadari (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2018)
This article discusses the integrative curriculum and its influence on graduate competencies, studies at the International Islamic University Malaysia Faculty of Economics. In accordance with the 1986 Memorandum of Degree Recognition, the curriculum and teaching method approach was developed by the International Islamic University Malaysia Faculty of Economics that is a comparative and integrative approach. That is, students are taught to master conventional and Islamic theories at once, and understand how to process the Islamization of conventional sciences that have developed today. Furthermore, if you look at the curriculum structure at the International Islamic University Malaysia Faculty of Economics, the existing courses can be divided into four categories. First, university compulsory courses (17 credits), compulsory faculties (36 credits), compulsory department courses (36 credits) and elective courses (36 credits). At present in IIUM four concentrations have been developed, namely Islamic economics, finance, international economics, and development economics. With the integrative curriculum developed by the International Islamic University Malaysia Faculty of Economics, it produces graduates who are professional, knowledgeable who are inspired by Islamic values and ethics that will develop Muslims and achieve progress in harmony with the ideals of Islam.